2021
DOI: 10.1017/s0714980821000362
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the Black Box of Managing Total Rewards for Older Professionals in the Canadian Financial Services Sector

Abstract: This study extends our knowledge about the management of older employees in the sector of financial services, which faces enormous transformational pressures (e.g., emergence of artificial intelligence, digital services). Based on the black box model of human resource management, we investigate how executives at 16 major financial institutions manage their total rewards to motivate their older professionals to stay at work longer. Top management’s views towards older professionals underlie a firm’s culture or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 72 publications
(115 reference statements)
0
1
0
Order By: Relevance
“…A longitudinal study has shown that among employees over the age of 50, a perceived lack of recognition increases the odds of work exit [84]. Indeed, if openness to age diversity in the workplace is essential to keeping older workers longer, it has been shown that openness towards older employees varies greatly from one organization to another in the finance services sector, going from weak or no particular support, case-per-case support, to strong formal and informal support [85].…”
Section: Meeting Older Employees' Relatedness Needs Through An Inclus...mentioning
confidence: 99%
“…A longitudinal study has shown that among employees over the age of 50, a perceived lack of recognition increases the odds of work exit [84]. Indeed, if openness to age diversity in the workplace is essential to keeping older workers longer, it has been shown that openness towards older employees varies greatly from one organization to another in the finance services sector, going from weak or no particular support, case-per-case support, to strong formal and informal support [85].…”
Section: Meeting Older Employees' Relatedness Needs Through An Inclus...mentioning
confidence: 99%